Considering photocatalytic activity of N/F/S-doped TiO2 thin films in degradation of textile waste under visible and sunlight irradiation. (December 2017) - Behpour, Mohsen; Foulady-Dehaghi, Rozita; Mir, Noshin
Highlights: F/Tu-TiO2 photocatalytic nano-layers were synthesized by dip-coating sol–gel method. Coated layers on glass spheres were investigated in degradation of textile waste. The photocatalytic activity were examined under visible and sunlight irradiation. TiO2 doped with 5% of fluorine showed the highest photocatalytic activity. Finally, 86–99% degradation has happened under both irradiations sources after 6 h. Abstract: Degradation of azo dyes as textile industry pollutants was investigated by photocatalytic process using F, N and S tri-doped TiO2 thin films immobilized on the glass spheres. Nanocatalyst thin films were successfully prepared via sol–gel dip-coating method. The immobilized TiO2 on the glass spheres were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDS), diffuse reflectance spectroscopy (DRS) and CHNS analysis. UV–Vis spectroscopy and chemical oxygen demand (COD) have been used in order to evaluate the degradation process. It was found that optimization of fluorine at 5% doping can give rise to the maximum decomposition of 86–100% within 6 h under visible irradiation. Also, according to the COD results, after 6 h, a reduction of the COD value from the azo dye solution was apparently obtained in same condition. The results showed that the synthesized nano-layers have good stability and reproducibility and therefore are potential to be used in various industrial processes.